Hubungan antara Usia, Jenis Kelamin dan Indeks Massa Tubuh dengan Kejadian Hipertensi di Rumkital Dr.Ramelan Surabaya - MARIA INGGRIT BELA THESMAN (Universitas Hang Tuah, 2019)
ABSTRACT Background : Hypertension or high blood pressure is heart and blood vessel disorder marked by increasing of blood pressure. The risk factors of high blood pressure are age, sex difference, body mass index, genetic, smoke, stress, physical activity, patterrn of natrium intake and dietary, consumption of alcohol and caffeine. Purpose : This observation purpose is to aknowledge the relations between age, sex difference and body mass index with incident of Hypertension. Method : The study design is observational analytic with cross sectional design, using secondary data recorded in the medical record in poly heart sub department intern at Rumkital Dr. Ramelan Surabaya in November 2017 . Technique sampling is using consecutive = purposive sampling method. Used 96 samples that meet the criteria for inclusion and exclusion. Data analysis of this research using statistic test Cramer's V Result : 54 person hypertension patient from 96 of the total sample. Result of this study showed there is correlation between age and hypertension incident, with value of p=0,031, < α=0,05. There is correlation between sex difference and hypertension incident with value of p=0,025 < α=0,05. There is correlation between Body mass index and hypertension incident with value of p= 0,000 < α=0.05. Conclution : Age, sex difference, body mass index (BMI) have a significant effect on the incidence of Hypertension.